(untitled) (CAHIERS MAGELLANES-NS, 2024)
Introduction: This review paper highlights the significance of Tinospora cordifolia (T. cordifolia) in the therapeutics, chemical constituents, and pharmacological activities. Tinospora cordifolia is an evergreen shrub belonging to the family of Menispermaceae and is broadly used in traditional medicine systems. This woody climbing shrub is generally recognized as “Guduchi” and “Amrita” and is disseminated in China, India, Srilanka and Myanmar. Method: The review data of T. cordifolia was collected from various scientific online search engines in particular PubMed, Science central, Web of Science, Science Direct, Scilit as well as Google Scholar. Various in vitro, in vivo, and clinical studies were added in this review by using different keywords like Tinospora cordifolia, Guduchi and Amrita. Results: The extract of numerous components of this plant such as stems, leaves, bark, and roots show potent antioxidant properties. In addition, Tinospora is reputed to possess antiallergic, antispasmodic, antiperiodic, anti-inflammatory, antipyretic, immunomodulatory and antitumor activities. T. cordifolia possesses a diverse range of active biological compounds from different phytochemical classes inclusive of alkaloids, sitosterols flavonoids, phenolic acids and terpenoids. Conclusion: T. cordifolia can be used as an effective therapeutic agent for the treatment of illnesses. Therapeutic properties of this plant led to the development of remedial products to cure a broad spectrum of illnesses.